(untitled) (Journal of Forensic Medicine & Toxicology, 2021)
Traumatic head injury due to blunt force impact constitutes maximum number of morbidity and mortality in clinical and medico-legal settings. Serious life-threatening injuries damage do occur when the victim is pushed or knocked to the ground, leading to striking of his head. The aim of the present study was to assess and outline the pattern of fatal cranio-cerebral damage sustained due to blunt force trauma. This was a three-year retrospective autopsy-based study from a tertiary care centre of rural southern Haryana. All the cases, where the cause of death was due to cranio-cerebral damage predominantly were included in the study. Out of total 143 cases of fatal head injury who succumbed to death, predominantly were males and were in age group of 15-45 year. Road traffic accidents was the leading cause of head injury while only few cases were as a result of assault. In hospital deaths, maximum patients died within 2 hours of hospitalisation. Analysis of all the head injuries showed the commonest injuries were scalp injuries followed by the life-threatening intracranial haemorrhages (SDH & SAH). Linear or fissured fracture predominates among different types of skull fractures and vault of skull was most likely to be fractured as compared to base of skull. Blunt trauma to the head is still a pertinent challenge for the autopsy surgeon who must thoroughly construe injury pattern and other findings at autopsy, and correlate all of the findings to make an accurate ruling of the cause and manner of death.